In vitro antimicrobial activity and formulation of herbal anti-acne gel containing Rhizophora stylosa fruits extract - Azrifitria Azrifitria; Sri Purwaningsih; Annisa Rahma Fatmala (Pharmaciana, 2022)
Mangrove fruits have a variety of bioactive metabolites that may control microbial growth. The present study was conducted to formulate and evaluate the antibacterial activities of Rhizophora stylosa fruit extract. The antibacterial activity of R. stylosa crude extract was investigated against Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acnes by disc diffusion method. The herbal gel formulations were developed using different concentrations of kappa carrageenan and Carbomer 940 as the gelling agent. The physicochemical characteristics and in vitro antibacterial activity of the gel were evaluated. The results revealed that the extract had a minimum inhibitory concentration value of 0.05 mg/ml against S. aureus and P. acne, and 0.1 mg/mL against S. epidermidis. All herbal gel formulations with 0.5% w/w of the extract showed a strong inhibitory activity against P. acnes. The herbal gel showed a good homogeneity, pH, viscosity, spreadability, and physical stability in an accelerated condition. Among all formulation studied, F1 was considered as the optimized formulation which contains 0.5% of the R. stylosa fruit extract with 0.25% kappa carrageenan and 0.5% Carbomer 940. It can be concluded that the developed gel formulation has potential against Acne vulgaris. Further research is needed to determine the safety and efficacy so R. stylosa can be developed as an alternative natural anti-acne agent.